Reproductive and trophic ecology of Ansonia minuta (Amphibia: Bufonidae) - Das, Indraneil; Direp, Yolande; Haas, Alexander (Malaysian Nature Society, 2009)
Reproductive and dietary ecology of Ansonia minuta was studied at Kubah National Park, Sarawak. A total of 22 individuals (12 males and 10 females) were examined to determine sexual size dimorphism, and dietary and reproductive characteristics. In this species, body size was not correlated with diet (as expressed in terms of stomach content weight or quantity of food ingested) or reproductive output (clutch size, egg size or clutch weight) in females. Males, however, showed a relationship between body size and stomach weight. Sexual size dimorphism was found to be significant in the species, with females being the larger of the sexes. Ansonia minuta is an ant-specialist, rarely consuming non-ant food resources.